125 Deterioration of Right Ventricular Function on Exercise Detected by Exercise Cardiac Magnetic Resonance Imaging in Patients with Pulmonary Arterial Hypertension. (3rd June 2016) - Jaijee, Shareen; Quinlan, Marina; Tokarczuk, Pawel; Statton, Benjamin; Berry, Alaine; Diamond, Tamara; Howard, Luke; Gibbs, Simon; O'Regan, Declan
Abstract : Introduction: Right ventricular (RV) function is a prognostic factor in patients with idiopathic PAH (iPAH). However at diagnosis, no factors differentiate those who will progress to RV dysfunction at 1 year. RV dysfunction in disease becomes more manifest on exercise and there is interest in the capacity of the RV to augment during exercise and its relationship with outcomes. Cardiac magnetic resonance imaging (CMR) is an accurate method of evaluating cardiac function during exercise. We aimed to study the ability of CMR to detect changes in RV and left ventricular (LV) function during exercise in healthy controls (HC) and patients with iPAH and hypothesised that RV dysfunction in iPAH becomes more apparent on exercise. Methods: Resting and exercise CMR was carried out on 10 HC (6 women, average age 36 ± 12) and 10 patients with iPAH (8 women, average age 37 ± 9) using a Philips 1.5T Achieva (Best, Netherlands) with a 32-channel cardiac coil. Supine exercise was performed using an MR compatible ergometer (Lode, Netherlands) at 40% of the watts achieved on cardiopulmonary exercise testing. Free breathing, real time LV short axis stack images were acquired during rest and exercise. LV and RV volumes were analysed using cvi42 (Circle Cardiovascular Imaging, Canada) using conventional endocardial surface segmentation. The Wilcoxon signed rank test was used to compare within groups and the Mann Whitney U test for between group analysis. Results: Results are summarised in Table 1 . HCs exercised at a mean of 81 ± 25W and patients at a mean of 44 ± 11W. In HCs, RV and LV stroke volume (SV) increased on exercise, driven by a decrease in RV and LV end systolic volume (ESV). LV and RV ejection fraction (EF) increased. In patients, LVEDV and LVESV decreased on exercise, with an increase in LVSV and LVEF. RVEDV increased in size with a trend for ESV to be higher than at rest. RVSV and RVEF remained unchanged. Between groups, at rest, LVESV and LVSV were lower in patients with no significant differences in RV function. However, on exercise, patients had a significantly higher RVESV and lower RVSV and RVEF, compared to HCs. Conclusion: Exercise CMR is a sensitive, accurate test which can determine physiological changes in RV and LV function. We have shown that on exercise, when compared to HC, the LV in patients with iPAH decreases in size, the RV increases in size and RV dysfunction becomes apparent which was otherwise not present at rest. This could potentially be valuable in the assessment of response to treatment and prognosis in patients with iPAH.